A new set of primers for COI amplification from purpleback flying squid (Sthenoteuthis oualaniensis) - Lei Xu; Qi Huang; Shaolin Xu; Xuehui Wang; Peng Zhang; Liang Xu; Feiyan Du (Mitochondrial DNA. Part B. Resources, 2017)
Despite the contribution of DNA barcoding towards understanding the biodiversity and distribution of species, the success of the mitochondrial cytochrome c oxidase subunit I gene (COI) amplification has been quite variable when it comes to Cephalopoda. Some species in this class such as Sthenoteuthis oualaniensis seem to be more difficult to amplify COI than others due to failed amplifications with universal primer and lack of specific set of primers. In this study, we developed new Sthenoteuthis – specific primer set, which significantly increased average amplification success. The new primer set will aid the recovery of barcodes from this difficult group and facilitate further studies in phylogeny and cryptic diversity of Sthenoteuthis oualaniensis.